GAYA HIDUP MODERN DALAM FIKSI ANAK SERIAL KECIL-KECIL PUNYA KARYA (KKPK) - Nugraha, Reza Sukma (JURNAL PESONA, 2016)
This article aims to explain modern life style identified in Kecil-kecil Punya Karya (KKPK) childrenâs fiction series. The modern life style is analyzed using Lucien Goldmanâs genetic structuralism. The result shows that childrenâs life style shown in three KKPK childrenâs fiction represents childrenâs modern life style in real life that is intended for consumerism and hedonism. This is a dilemma for childrenâs literature development. However, childrenâs literature serves as mean of eduction for children, but on the other side, modern life style shown does not deserve to be role model for children.Keywords: modern life style, childrenâs literature, genetic structuralism, Goldman